Development of strategies for the incorporation of microbial pesticides into the integrated management of migratory pests - Lomer, C.J.; Bateman, R.P.; Dent, D.; Groote, H. de; Douro-Kpindou, O.K.; Kooyman, C.; Langewald, J.; Johnson, D.L.; Peveling, R.; Thomas, M.B. (1999)
1 Effective biological pesticides based on oil formulation of deuteromycete fungal spores have been developed for use against locusts and grasshoppers. The isolate IMI 330189 of Metarhizium anisopliae (¯avoviride) var. acridum has been registered, extensively ®eld tested and its operating characteristics explored. It should form an powerful component technology in the integrated management of locust and grasshopper pests. 2 The particular advantages of Metarhizium anisopliae were found to be ef®cacy and persistence, low vertebrate toxicity, little environmental impact, conservation of natural enemies and potential for recycling. Additional socio-economic advantages include the possibility of local production, ease of disposal and versatility in use. The principal disadvantages relate to operating characteristics such as slower speed of kill and slightly greater lability in storage than chemical pesticides. 3 Strategies are being developed to integrate biological control agents into locust and grasshopper management schemes; for Metarhizium the accent is placed on: (i) treating the pest before it invades crops and (ii) situations with a high premium on environmental issues. 4 For some pest situations, fast-acting chemical pesticides will still be necessary for crop protection. 5 A cheaper biological agent, such as Nosema locustae, with the capacity to persist in the pest insect population would be useful. Research is recommended on the long-term impact of Nosema in Africa. 6 An evaluation of the utility of the manual destruction of egg pods leads to the conclusion that we should consider the possibility of importing egg parasitoids, such as Scelio parvicornis from Australia, into Africa. 7 Further development work is needed to clarify the economics and politics of locust and grasshopper control; to improve the regulatory framework for biopesticides; to inform key decision makers of the availability and potential of Metarhizium; and to implement the bio-intensive IPM strategies described.